Effectiveness of Corporate Social Responsibility and Information Communication Technology in Organizational Change Management (Global Journal of Management and Business Research, 2013)
This paper explains the concept of corporate social responsibility and examines the use of corporate social responsibility in organizational change management. The concept of CSR is well researched but implementation of CSR is not well researched. Here we examine the role of ICT and how it affects CSR. In this paper we see how ICT and CSR facilitate the implementation of change in organization along with the issues which an organization faces in the processes of managing change.
Keywords: HRM; human capital; competitive advantage; human resource